Cognitive theory of metaphor and Jerzy Wróblewski’s concept of legal interpretation - Zalewska, Monika (Hybris, 2017)
Jerzy Wróblewski is one of the most prominent and influential legal theorists in Poland. His theory of legal interpretation containing a division into linguistic, systemic and functional dimension is highly regarded by Polish legal community. However, when formulating the theory Wróblewski was aware that his theory lacks some elements. In his work he points out that despite three dimensions the result of the interpretation is still unpredictable. For instance, interpreter’s personality might be additional factor influencing legal interpretation process. In this context, Wróblewski compares the lawmaker to a composer and a subject making legal interpretation to a musician performing a piece of music. Wróblewski emphasizes the importance of such factors. However, an interpreter should disregard additional factors in the process of legal interpretation. At the time, when Wróblewski formulated his theory, the cognitive science was not developed yet. Nowadays, Lakoff Johnson’s idea of conceptual metaphors is widely known and might be one of the missing elements Wróblewski had in mind. This paper will examine such possibility and its consequences. Firstly Wróblewski’s theory of legal interpretation will be presented. Next, I will move to a brief description of Lakoff-Johnson theory. Then, it will be discussed if such approach is possible in terms of Wróblewski’s theory. Finally, the necessary modification of legal interpretation theory will be analyzed. In this part, the key question is whether the metaphorical aspect is a new dimenson of legal interpretation.